A Case Series: Continuous Kidney Replacement Therapy in Neonates With Low Body Weight - Wu, Chen-Yu; Lin, Yung-Chieh; Chen, Chih-Chia (Frontiers in Pediatrics, 2021)
Emerging data indicate that acute kidney injury (AKI) may contribute to a worse prognosis in the infant population. Kidney replacement therapy (KRT) can be used to treat patients with AKI; however, this technique is challenging in neonatal intensive care units (NICU) due to the low body weights and blood volumes in this population. Peritoneal dialysis (PD) is a potential modality since it is technically less challenging. However, PD has been associated with several disadvantages, including poor fluid status control, catheter-associated leakage, and peritonitis. Unfortunately, these complications can cause the temporary cessation of PD. Continuous kidney replacement therapy (CKRT) may represent a suitable alternative for PD. CKRT may be technically feasible in infants; however, little is known about the application of CKRT in neonates with low body weights. In this report, we discuss three cases of CKRT who were treated in the NICU at a tertiary medical center in southern Taiwan. We selected an adequate catheter diameter and achieved vascular access via an internal jugular vein or umbilical vein. The prescription of an appropriate dose of heparin was then used to prolong the circuit life of the CKRT. The maintenance of circuit durability in neonates with low body weight remains problematical. We hope that our experience can assist with the future clinical management of CKRT in neonates with low body weight.